Conflicts of truth: Foucault and Habermas in dispute - Posselt, Gerald (Rivista Italiana di Filosofia del Linguaggio, 2024)
While it is usually assumed that conflicts have little to do with truth, the article argues that fundamental socio-political conflicts are always also conflicts of truth. Tosupport this thesis, the conceptual history of the term conflict is first outlined. This shows that the modern sociological concept of conflict highlights the forces and power relations at work in social systems but largely ignores the linguistic and epistemic dimensions of conflict. To address this shortcoming, Habermas’s linguistic and truth-theoretical foundation of sociology and Foucault’s concept of the regime of truth are contrasted with each other. Habermas emphasizes the dissensual character of truth claims and points out that it is the participants’ orientation towards truth that drives conflicts. However, insofar as he conceives of truth as a transcendental reference point located outside the experiential reality of social actors, he overlooks the genuine socio-political dimension of conflicts of truth. By contrast, Foucault allows us to see socio-political upheavals as crises or conflicts that affect a society’s regime of truth, understood as the complex interplay of governmental techniques, subjectivation practices, and forms of truth-telling.